Автоматизовані системи контролю та забезпечення безпеки на шахтарських об’єктах - Дрогіна, О. (ХНУРЕ, 2023)
The paper examines the development of automated control systems and ensuring the safety of mining operations. The main purpose of the study is to determine the advantages of automated control and safety systems at mining facilities and to determine their effectiveness in preventing accidents and improving overall safety. The study examines the application of various technologies, such as sensors, cameras, and unmanned aerial vehicles, to detect and prevent dangerous situations in mining enterprises. Evidence shows that automated control and safety systems significantly reduce the risks associated with mining operations and increase overall worker safety